Biossorção de corantes têxteis utilizando biomassa fúngica residual - Zavilenski, Ana Isabela (2022)
Fungal biomass produced during fermentation to obtain enzymes or other metabolites is often unused and discarded. Depending on the culture medium and conditions, a large volume is generated, requiring proper disposal. This biomass can be used as a biosorbent in effluent treatment. Textile industries are the biggest consumers of paints and water in their processing processes, mainly in laundry and dyeing. Disposing this generated effluent becomes an environmental problem, as many are toxic and mutagenic. Currently, physicochemical processes are used to remove those that are often expensive and inefficient. Thus, studying alternative ways of treating these more viable effluents becomes necessary. The biomass used in this project is produced by Botryosphaeria ribis EC01 fungus in an optimized medium for the production of lipases. The biomass used for the treatment of the synthetic reactive dye solution was prepared in two different ways, the first lyophilized and the second autoclaved and dried in an oven. Both were characterized by the techniques of Thermogravimetric Analysis (TGA), Nitrogen Physisorption, Charge Point Zero (pHPCZ), Characterization by Fourier Transform Infrared Spectroscopy (FTIR) and Scanning Electron Microscopy (SEM). The treatment of the synthetic dye solution was carried out based on a 23factorial design for the lyophilized biomass obtained discoloration of up to 80.32% in 165 minutes with a dye concentration of 55 mg L1 and 125 mg of biomass. While with autoclaved biomass obtained discoloration of up to 47.06% in 165 minutes with a dye concentration of 55 mg L1 and 200 mg of biomass. From the optimal conditions, pH and temperature were varied, in which the temperature was not a determining factor to contribute to the discoloration because, with its increase, there is a decrease in the adsorbed capacity. However, the pH variation provided an increase in the percentage of discoloration. Through this work, it was possible to decolorize the synthetic solution of reactive dye with residual fungal biomass, in which the biosorbent proved to be efficient in the treatment.